SHEAR STRENGTH OF HEAT-TREATED TALI (ERYTHROPHLEUM IVORENSE) AND IROKO (CHLOROPHORA EXCELSA ) WOODS, BONDED WITH VARIOUS ADHESIVES - Hamiyet Sahin Kol; Günay Özbay; Suat Altun (BioResources, 2009)
The aim of this study was to evaluate the effect of heat treatment on the shear strength of tali (Erythrophleum ivorense) and iroko (Chlorophora excelsa) woods, bonded with some structural adhesives. Shear strength of untreated and heat-treated woods bonded with phenol-formaldehyde (PF), melamine-urea-formaldehyde (MUF), melamine-formaldehyde (MF), and polyurethane (PUR) adhesives was studied. An industrial heat treatment method (ThermoWood) was used. The timbers were thermally modified for 2 hours at 180 ºC. Laminated samples having two sample sets were prepared from untreated and heat-treated wood for the shear strength test. The results of the tests showed that the heat treatment affected shear strength of laminated wood negatively. Although there was a considerable difference in adhesive bond shear strength between untreated and treated wood, both wood species bonded with the adhesives fulfilled the required value for shear strength of the adhesive bonds. PF, MUF, MF, and PUR adhesives performed in a rather similar way for both wood species.